7(9x-1)=2(9x+1)+846

Simple and best practice solution for 7(9x-1)=2(9x+1)+846 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(9x-1)=2(9x+1)+846 equation:


Simplifying
7(9x + -1) = 2(9x + 1) + 846

Reorder the terms:
7(-1 + 9x) = 2(9x + 1) + 846
(-1 * 7 + 9x * 7) = 2(9x + 1) + 846
(-7 + 63x) = 2(9x + 1) + 846

Reorder the terms:
-7 + 63x = 2(1 + 9x) + 846
-7 + 63x = (1 * 2 + 9x * 2) + 846
-7 + 63x = (2 + 18x) + 846

Reorder the terms:
-7 + 63x = 2 + 846 + 18x

Combine like terms: 2 + 846 = 848
-7 + 63x = 848 + 18x

Solving
-7 + 63x = 848 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
-7 + 63x + -18x = 848 + 18x + -18x

Combine like terms: 63x + -18x = 45x
-7 + 45x = 848 + 18x + -18x

Combine like terms: 18x + -18x = 0
-7 + 45x = 848 + 0
-7 + 45x = 848

Add '7' to each side of the equation.
-7 + 7 + 45x = 848 + 7

Combine like terms: -7 + 7 = 0
0 + 45x = 848 + 7
45x = 848 + 7

Combine like terms: 848 + 7 = 855
45x = 855

Divide each side by '45'.
x = 19

Simplifying
x = 19

See similar equations:

| -14+126x=14+84x | | 13x+89=180 | | 2x-(x+7)+9= | | 12n(n+3)+15=396 | | 22=3y+x | | 7(18x-2)=14(6x+1) | | 5(2x+3)(4x-1)=0 | | 7x+15=6x+20 | | 0.25(4x-2)=x-.25 | | 4x+8y-2(7x-4y)= | | 63+8(6x-1)=7(6x+1) | | -8(b-862)=-560 | | 16=8c | | 2.50(m+15.00)=662.5 | | 2.5r=95 | | 6(3x-6)=10x | | a+3ab+6+7a-2ab-1=0 | | 75+5x=10x+100 | | 9b-7b+6=-4b+78-3b | | 11x-160=56-7x | | 10+58=6x+2 | | 2x^4+3x-50=0 | | 5a+4b-5(7a-9b)= | | 26w+20=956 | | X-2x=125 | | (1+y)x^2-3yx+(1-y)=0 | | 2.50(m+15.00)=412.5 | | 84=2x-4+2x+4 | | 75=4529 | | -1-10r^2=-881 | | 3.4=y+2.1 | | -3x^2+8x-6=0 |

Equations solver categories